KONTRIBUSI FINANCIAL TECHNOLOGY PEER-TO-PEER LENDING SEBAGAI PERMODALAN DIGITAL UNTUK MEMBANTU PEMBIAYAAN PETANI DALAM MENINGKATKAN PRODUKTIVITAS USAHA TANI - Jhon Eferedy; Apip Alansori; Kadek Widani; Dicky Fardiansyah Nugroho; Neshwa Eka Ramadona (Jurnal Ilmiah Akuntansi Rahmaniyah, 2026)
This study examines the role of Fintech peer-to-peer (P2P) lending as an alternative source of digital financing for farmers facing agricultural funding challenges due to declining productivity, particularly in West Lampung Regency affected by the El Niño phenomenon. A qualitative descriptive approach was employed through literature and document analysis, supported by primary data collected from direct interviews with local farmers. The data were obtained from scientific publications, official documents, and interview results, then analyzed using a narrative approach. The findings indicate that limited access to conventional financial institutions makes it difficult for farmers to secure capital after crop failure. Fintech P2P lending offers a faster, more flexible, and collateral-free financing option; however, its adoption remains limited because of low digital literacy and concerns about data security. The study is limited by the small number of participants, which may not fully represent farmers across Lampung. It contributes to the fields of digital agriculture, financial inclusion, and agricultural technology while providing insights for local governments, OJK, and Fintech providers in developing farmer education programs. Its novelty lies in linking climate change impacts with technology-based digital financing in a local agricultural context.